Photodegradation of methanol under UV-visible irradiation by titania dispersed on polyester cloth - Bhattacharyya, Kaustava; Tripathi, Arvind K.; Gupta, Narendra M.; Tyagi, Avesh K. (Photochemistry and Photobiology, 2010)
Titania supported on polyester fabric (TiO(2)-PY) with varying titania loadings (2-7 wt%) were prepared via the dip-coating method at room temperature using an aqueous slurry of anatase titania. Structural and morphological characterizations by X-ray diffraction and scanning electron microscopy revealed that the titanium dioxide crystallites deposited on the surface of the polyester fabric were in the micrometer range while their phase remained to be anatase. Photocatalytic activity of TiO(2)-PY fabric catalysts was evaluated for vapor-phase oxidation of methanol in air as a test reaction in the presence of UV as well as solar radiation under ambient conditions. These catalysts were found to be quite active in both UV and solar irradiation with activity being higher in the former case. CO(2) yield from photo-oxidation of methanol depended on titania content and also on its dispersion over polyester fabric support.